Antiangiogenic approaches for the treatment of advanced synovial sarcomas - Do, Khanh (Curr Opin Oncol, 2012)
PURPOSE OF REVIEW: Synovial sarcomas are regarded as chemosensitive tumors compared to other types of soft tissue sarcomas, however, prognosis for advanced refractory disease remains poor. In light of the vascular nature of sarcomas, current molecularly targeted therapies aim at an antiangiogenic approach to management of this disease. RECENT FINDINGS: Recent studies with oral vascular endothelial growth factor receptor (VEGFR) inhibitors such as sunitinib, sorafenib and cediranib have shown disease stabilization in patients with advanced synovial sarcoma. Forty-nine percent of patients with synovial sarcoma on the phase II trial of pazopanib had no evidence of disease progression at 12 weeks. SUMMARY: The overall impact of chemotherapy on survival has been minimal in advanced soft tissue sarcomas. Anti-VEGF therapies have resulted in improved outcomes for patients with various solid tumors, and have shown preliminary evidence of activity in synovial sarcomas. Combinations of anti-VEGF therapies with agents targeting other pathways dysregulated in sarcomas have the potential to improve the outcome of this difficult-to-treat disease.